Analysis of the temperature drop rate before and during snow events in Santa Catarina - Mintegui, Jéssica Melo (2018)
In this work the average behavior of minimum and maximum temperatures for the state of Santa Catarina, before and during snowfall events, from 1979 to 2015, was analysed. To accomplish this study, have been employed minima and maxima temperature data from conventional meteorological stations which were provided by the Centro de Informações de Recursos Ambientais eHidrológicos de Santa Catarina (Ciram), linked to the Empresa de Pesquisa Agropecuária e Extensão Rural de Santa Catarina (Epagri). In general, a sharp decreses in temperatures from day D - 1 (the day before the snow event) to day D + 0 (day of snowfall) is observed.